2009 7th International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks 2009
DOI: 10.1109/wiopt.2009.5291569
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on the information propagation delay in interference-limited ALOHA networks

Abstract: Abstract-In a wireless network the set of transmitting nodes changes frequently because of the MAC scheduler and the traffic load. Analyzing the connectivity of such a network using static graphs would lead to pessimistic performance results. In this paper, we consider an ad hoc network with half-duplex radios that uses multihop routing and slotted ALOHA for the network MAC contention, and introduce a random dynamic multi-digraph to model its connectivity. We first provide analytical results about the degree d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Let us now discuss the relation of our results to those obtained in [11] and [14]. In these papers the so-called delay-tolerant networks are considered and modeled by a spatial SINR or SNR graph with no time dimension.…”
Section: Sinr Space-time Graph and Routeingmentioning
confidence: 70%
“…Let us now discuss the relation of our results to those obtained in [11] and [14]. In these papers the so-called delay-tolerant networks are considered and modeled by a spatial SINR or SNR graph with no time dimension.…”
Section: Sinr Space-time Graph and Routeingmentioning
confidence: 70%
“…Poisson models also allow one to discover some theoretical limitations of macroscopic properties of MANETs, e.g. the scaling of the capacity of dense and/or extended networks [13,14], or the speed of packet progression on long routes [3,15].…”
Section: Related Workmentioning
confidence: 99%
“…This model adds directionality to the network where the possible edge set varies with time. By considering a connection function where two nodes connect if they form a receiver-transmitter pair, a noise condition is met and there is no intermediary node that is transmitting, [Gan09a] showed that the time for a path to form between a source and destination scales linearly with their Euclidean separation. Moreover, [Bac10a] highlighted that for the SIR model there is a phase transition for a critical transmit probability ℘ where the mean delay becomes infinite.…”
Section: Temporal Networkmentioning
confidence: 99%